1995
DOI: 10.1046/j.1365-2648.1995.21010095.x
|View full text |Cite
|
Sign up to set email alerts
|

Struggling to maintain balance: a study of women living with fibromyalgia

Abstract: Thirty-six women with fibromyalgia (FM) were asked to describe how they live with their FM. Data were analysed using the constant comparative method. The goal was understanding the process of living with FM through theory development. The women described living with FM as struggling to maintain balance; this involves recalling perceived normality, searching for a diagnosis, finding out and moving on (transcending the illness). Several women relinquished the struggle because of situations that may or may not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 12 publications
2
51
0
Order By: Relevance
“…The team members did not agree over 24 papers and sent these to two other team members for a decision. Sixteen studies were excluded after quality appraisal, [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] hence 77 papers were included reporting 60 studies. These studies explored the experiences of 1168 adults ranging from 18 to 91 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…The team members did not agree over 24 papers and sent these to two other team members for a decision. Sixteen studies were excluded after quality appraisal, [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] hence 77 papers were included reporting 60 studies. These studies explored the experiences of 1168 adults ranging from 18 to 91 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Resilience for the purpose of this paper refers to an individual's ability to "bounce back" and adapt to or recover from an adverse event [17]. This has been explored as a potential mediator in a range of adverse or traumatic experiences including those experienced as a result of living with and managing long term physical and mental health conditions [18][19][20][21][22][23][24]. Resilience has been suggested as an underpinning reason that determines a person's ability to selfmanage their disease [25] and so may play a significant role in shaping psychosocial support offered to patients with COPD and CHF in the future.…”
Section: Introductionmentioning
confidence: 99%
“…One of the particularities that can be found in FM patients is the narrated importance of obtaining a clinical diagnosis and, thus, an external validation of their suffering given the absence of "visible" symptoms to others (e.g. Cunningham & Jillings, 2006;Hellström et al, 1999;Schaefer, 1995;Undeland & Malterud, 2007). Moreover, several studies have shown that FM has impact on different life contexts of individuals living with such a chronic condition (e.g., Aïni et al, 2010;Arnold et al, 2008;Asbring, 2001;Cunningham & Jillings, 2006;Söderberg & Lundman, 2001), and some of them have stressed specific dimensions, such as professional life (Gauer, 2009;Liedberg & Henriksson, 2002), couple relationship (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the finding and evolution of adaptive coping strategies in the context of FM tend to assume an important role in living with FM (e.g. Cunningham & Jillings, 2006;Hellström et al, 1999;Schaefer, 1995Schaefer, , 1997Söderberg & Lundman, 2001). Another meaning-making process identified in FM patients' narratives is related to the perceived control over symptoms (e.g., Asbring, 2001;Hellström et al, 1999), which can range from perceived absence of control to a perceived total control over symptoms.…”
Section: Introductionmentioning
confidence: 99%